2005
DOI: 10.1645/ge-322r
|View full text |Cite
|
Sign up to set email alerts
|

Artemether as Adjuvant Therapy to Praziquantel in Murine Egyptian Schistosomiasis Mansoni

Abstract: We investigated the activity of artemether (ART) against different developmental stages of schistosomes alone and in addition to praziquantel (PZQ). ART was administered orally (400 mg/kg) 4 and 6 wk postinfection (PI), 4 and 5 wk PI, or 4 or 6 wk PI alone and in addition to oral PZQ (500 x 2 mg/kg) 6 wk PI. Mice were killed in parallel to infected untreated controls 8 wk PI. Parasitological parameters and histological changes in the liver were studied. ART given 4 and 6 wk PI reduced worm burdens by 59 and 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 19 publications
4
20
2
1
Order By: Relevance
“…In a subsequent study, it was found that, compared with praziquantel alone, combined treatment of praziquantel and artemether (4 and 5 weeks or 4 and 6 weeks post-infection) in mice infected with the Egyptian strain of S. mansoni did not enhance worm eradication, but there was a complete absence of parasite eggs (Mahmoud and Botros 2005). Therefore, an effect on the fecundity of female worms could be concluded.…”
Section: Combination With Praziquantelmentioning
confidence: 97%
See 3 more Smart Citations
“…In a subsequent study, it was found that, compared with praziquantel alone, combined treatment of praziquantel and artemether (4 and 5 weeks or 4 and 6 weeks post-infection) in mice infected with the Egyptian strain of S. mansoni did not enhance worm eradication, but there was a complete absence of parasite eggs (Mahmoud and Botros 2005). Therefore, an effect on the fecundity of female worms could be concluded.…”
Section: Combination With Praziquantelmentioning
confidence: 97%
“…Xiao and Catto (1989b) showed that artemether had also an effect on 35-to 56-day-old adult worms of S. mansoni with total worm reduction rates of 30-51%, although it was most effective against schistosomula. There is also some difference in the sex-related susceptibility of the adults where adult female worms have been found to be somewhat more susceptible to artemether than males (Mahmoud and Botros 2005).…”
Section: Species and Stage Specificitymentioning
confidence: 99%
See 2 more Smart Citations
“…Artemisine has been proven to be partially active against juvenile forms of Schistosoma in murine models, 5 in which it has drastically reduced the egg burden when given between weeks 4 and 6 postinfection. Some human studies have also indirectly demonstrated a significant reduction in egg burden when artemisine was used in therapeutic doses, both in the acute and chronic phases of infection.…”
Section: Response To Lettermentioning
confidence: 99%